PELATIHAN SENAM SIGINJAI PADA CLUB SENAM PAGI SUNGAI KAMBANG CERIA (SPSKC) - Fitri Diana; Sukendro Sukendro (Cerdas Sifa Pendidikan, 2019)
ABSTRACT Physical activity is any body movement produced by skeletal muscle that requires energy expenditure. Non-existent physical activity is an independent risk factor for chronic diseases and overall is thought to cause death globally. Doing sports activities have many goals including to maintain and improve health and fitness. Through sports can be developed not only physical skills, but also mental, spiritual, emotional and intellectual skills. Besides that, the purpose of sports activities is to improve human quality. Many physical activities that can be done to improve physical fitness are light running, walking, swimming, playing tennis, gymnastics and so forth. This sport is a form of exercise that can increase endurance of the pulmonary heart. SPSKC Club is a cheerful kambang river morning gymnastics club, this club always holds gymnastics every Sunday morning at GOS Sungai Kambang. According to the gym club administrator, participants this morning experienced a decrease in interest due to start experiencing boredom, after being found out by the management it turns out that the standard gymnastics given is monotonous which is always done almost every week. Based on the existing problems in the field, an idea was born to give siginjai gymnastics training to the cheerful kambang river morning gymnastics club in hopes of eliminating boredom for club members. Kata Kunci : Training, Siginjai Gymnastics